Analyzing the Implementation of Village Regulations in Ulak Pandan Village, West Merapi Subdistrict, Lahat Regency: A Descriptive Study - Budianto, Kun (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2025)
With the enactment of Law No. 6 of 2014, a new era of empowering rural communities began, enabling them to define their roles, set priorities, and exercise authority. The objective was to promote economic prosperity and cultural recognition for villages, as they function as the backbone of village democracy, reflecting independence and local community growth. This aspiration is embodied in the fundamental principles of the regulation, which emphasize a blend of recognition and subsidiarity concepts. Consequently, understanding the policies adopted by Village Leaders in community development and the process of formulating village regulations in line with Law No. 6/2014 became essential. The research problem was formulated within the framework of the Village Law, supported by Presidential Regulation No. 43 of 2014, focusing on the implementation of Law No. 6/2014 regarding villages and examining the process of village regulation development. The theoretical framework of Inu Kencana Syafiie’s Coordination Theory served as a lens through which this descriptive-analytical study explored the challenges faced by rural communities. The authors employed field research to examine how the formulation of village regulations in West Merapi Subdistrict, specifically in Ulak Pandan Village, Lahat Regency, aligns with the provisions of Law No. 6/2014 on village governance.